2018
DOI: 10.1016/j.cophys.2018.08.004
|View full text |Cite
|
Sign up to set email alerts
|

The intertwined roles of circadian rhythmsand neuronal metabolism fueling drug reward and addiction

Abstract: Drug addiction is a highly prevalent and devastating disorder with few effective treatments, resulting in enormous burdens on family and society. The cellular and behavioral effects of drugs of abuse are related to their abilities to elevate synaptic dopamine levels. Midbrain dopaminergic neurons projecting from the ventral tegmental area to the nucleus accumbens play crucial roles in substance-induced neural and behavioral plasticity. Significantly, increasing work suggests that interplay between the brain ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 147 publications
(148 reference statements)
1
5
0
Order By: Relevance
“…Functionally, previous work in the brain also showed that bromocriptine functions as an α 2A -AR agonist in the chicken pineal gland to suppress circadian increases in melatonin synthesis ( Zawilska and Iuvone, 1990 ). Bromocriptine’s actions on adrenergic receptors may therefore offer a novel mechanism for the drug’s ability to modify circadian regulation of catecholamine signaling in the CNS and periphery ( Cincotta et al., 1993 ; Freyberg and Logan, 2018 ; Holt et al., 2010 ; Wei et al., 2020 ). Similarly, in adipocytes, bromocriptine diminishes adipogenesis, lipogenesis, and obesity-related inflammation via α 2A -AR agonism ( Mukherjee and Yun, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, previous work in the brain also showed that bromocriptine functions as an α 2A -AR agonist in the chicken pineal gland to suppress circadian increases in melatonin synthesis ( Zawilska and Iuvone, 1990 ). Bromocriptine’s actions on adrenergic receptors may therefore offer a novel mechanism for the drug’s ability to modify circadian regulation of catecholamine signaling in the CNS and periphery ( Cincotta et al., 1993 ; Freyberg and Logan, 2018 ; Holt et al., 2010 ; Wei et al., 2020 ). Similarly, in adipocytes, bromocriptine diminishes adipogenesis, lipogenesis, and obesity-related inflammation via α 2A -AR agonism ( Mukherjee and Yun, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fentanyl self-administration in Sprague-Dawley rats has also been shown to increase expression of cytokines (e.g., interleukin (IL)1β, IL5), chemokines, tumor necrosis factor α (TNFα), and interferon proteins (e.g., IFNβ and IFNγ) in the NAc 68 . Our mouse proteomic data add to these previous studies, furthering a need for functional investigation into immune-and metabolic-related mechanisms underlying OUD and potential interactions with the circadian system [69][70][71][72] .…”
Section: Discussionmentioning
confidence: 58%
“…The most significant finding of our current study was that the circadian entrainment pathway, which plays an important role in helping organisms cope with dynamic environmental changes and maintain survival with adaptive behavior, was involved in susceptibility to MA addiction (30). In mammals, the circadian entrainment pathway consists of two parts.…”
Section: Analysis Of Dmr Data Inferred the Role Of The Circadian Entrmentioning
confidence: 61%